Hubungan Peran Orang Tua dengan Sikap Remaja tentang Seks Bebas - Dian Lutfinawati; Intin Ananingsih (Journal of Ners and Midwifery, 2014)
Teenagers are the transition from children into adults whose duration varies depends on the social and cultural factors. Parents take an important role to improve the general knowledge of child and adolescent reproductive health in particular. Method: The research design was correlational design. The research sample was 30 student XI class in MAN Wlingi, Blitar Regency. It was choosen using purposive sampling. The data was collected using questionnaire. The data was analysed using Chi Square Test. Result: The results showed by Chi Square correlation (Rho) that theÂ  p value = 0,001. Discussion: Based on the results of the research, it was recommended that parents not fully apply the authoritarian role to the teenagers